Multistakeholder collaboration in identifying rooftop solar power plant potential in Mandiri Energy Village, Kedungrong, Yogyakarta - Masrur Alatas; Agus Maryono; Ahmad Fudholi; Edy Herianto Majlan; Faiz Zamzami; Arisman (Interaction, Community Engagement, and Social Environment, 2026)
Background: Indonesia has significant solar energy potential due to its equatorial location, but its use remains suboptimal. This study aims to examine the installation of a pilot solar panel system in Kedungrong Village, Yogyakarta, as part of long-term plan in building an energy independent village. Methods: This study used a quantitative descriptive approach, with primary data in the form of field observations and system testing and secondary data in the form of solar irradiation data. The study location was in the Kedungrong Energy Independent Village, Yogyakarta, where 53 houses were identified as having the potential for rooftop PV installation. One sample was selected for system design using a 300 Wp solar panel integrated with supporting components. Results: The average solar irradiation reached 4.80 kWh/m²/day. The PV system produced a stable and reliable output voltage of 223.7 V AC for household needs. From an economic perspective, the investment cost of IDR 3,859,500 is considered affordable. Furthermore, observation results revealed that multi-stakeholder engagement involving academics, government, the community, and industry play a crucial role in supporting the program's implementation and sustainability. Each stakeholder contributed to the planning, implementation, coordination, and system use of the project to enhance its sustainability. Conclusion: The rooftop solar PV system is technically, economically, and socially feasible for household implementation and can support community-based sustainable energy development. Novelty/Originality: The novelty of this research lies in the integration of technical and economic analysis with a multi-stakeholder collaborative approach can a viable and sustainable community-based rooftop solar PV system.